Acne – Affect Elegance And Emotional Health – Homoeopathic Skin Care (Homoeopathy for All, 2022)
Even mild acne can affect one’s  emotional health. This is especially  true for teenage girls. In studies, teen  girls often say that acne makes them  feel unattractive. Acne is one of the  most common skin conditions in all  age groups, especially teenagers.  The clinical presentation of acne can  range from a mild comedonal form  to severe inflammatory cystic acne  of the face, chest, and back. This  article reviews causes, risk factors,  different types, clinical presentation  general management including  some home remedies management  and homoeopathic way of treatment  of acne. Homoeopathy treats the  person as a whole. It means that  homoeopathic treatment focuses  on the patient as a person and his  pathological condition.
Keywords: teenage girls; risk factors; different types